# algebra

posted by .

factor f(x)=4x^(3)+19x^(2)-149x+36 into linear factors if f(x)=-9

• algebra -

after a few tries I found f(4) = 0
so (x-4) is a factor
by synthetic long division I got
(x-4)(4x^2 + 35x - 9)
= (x-4)(x+9)(4x - 1)

What does the fact that
f(x) = -9 have to do with it.?

Did you mean to say: f(9) = 0 , that would have given me the clue that x+9 is a factor.

## Similar Questions

1. ### math,algebra

Can someone explain this to me plese: to factor a number you.... and then can you explain to me To factor an algebraic expression into prime factors means..... thanks This is how I would complete these two sentences. To factor a number, …
2. ### algebra

3ax^2 - 27a You can factor that into 3a (x^2 - 9), which also equals 3a(x-3)(x+3). It is not clear from your question what you are supposed to do with that algebraic expression. If it were equal to zero, x would be +3 or -3. If you …
3. ### Algebra

Factor: 3x^2 - 27 3x^2-27=0 27+(3x^2-27)=0+27 3x^2=27 (3x^2)/3=27/3 x^2=9 x=3 Since there is 3x^2, one term must contain 3x and the other x. 27 factors into 3*3*3 or 3*9. With this information, you should be able to factor it yourself. …
4. ### Algebra

use factor theorem to determine whether x+2 is a factor of f(x). if it is, write f(x) in factored form. f(x)=9x^3+24x^2+19x+14; x+2
5. ### Algebra

Find the product (1 - 3x) (x^2 - 6x - 4)x^2 A. -3x^5 + 19x^4 + 6x^3 - 4x^2 B. -3x^5 - 19x^4 + 6x^3 - 4x^2 C. -3x^5 + 19x^4 - 6x^3 - 4x^2 D.-3x^5 - 19x^4 - 6x^3 - 4x^2
6. ### math help

Factor f(x) into linear factors given that k is a zero of f(x). f(x)=x^3+(12-4i)x^2+(32-48i)x-128i, k=4i In completely factored form, f(x) =____ (factor completely. simplify your answer)